Progress in ethical practices of businesses - Peris-Ortiz, Marta; Márquez, Patricia; Gomez, Jaime A.; López-Sieben, Mónica (Springer, 2021)
The aim of this chapter is to describe the basic theoretical aspects of ethical practices in business and to present the remaining 15 chapters which comprise this book. An essential feature of this chapter is how ethics arises from specific economic facts and on the other hand, how the evolution of society, new resources, new technologies, and economic growth in developed countries lead to a cultural evolution which changes the traditional perspective on the obtainment of pro!ts, as reported by the Business Roundtable in their latest annual statement: not only the obtainment of pro!ts for the shareholders but also the obtainment of economic, social, and ecological benefits for all the stakeholders. This is the purpose and final goal of business ethics and the different chapters included in this book. RESUMEN El objetivo de este capítulo es describir los aspectos teóricos básicos de las prácticas éticas en los negocios y presentar los 15 capítulos restantes que componen este libro. Una característica esencial de este capítulo es cómo la ética surge de los hechos económicos y por otro lado, cómo la evolución de la sociedad, los nuevos recursos, las nuevas tecnologías y el crecimiento económico en los países desarrollados conducen a una evolución cultural que cambia la perspectiva tradicional sobre la obtención de beneficios, según informa Business Roundtable en su última declaración anual: no sólo la obtención de utilidades para los accionistas sino también la obtención de beneficios económicos, sociales y ecológicos para todos los grupos de interés. Este es el propósito y el objetivo final de la ética empresarial y los diferentes capítulos incluidos en este libro.
The ethical dimension in corporate and management behavior
Chapter 1 Pages 1 - 11
Keywords: Business ethics; Corporate social responsibility; Management behavior; Stakeholders; Ethical practices; Campus Mexicali